Waves and associated currents–experiences from 5 years metocean measurements in the northern North Sea. (January 2019) - Bruserud, Kjersti; Haver, Sverre
Abstract: To acquire sufficient simultaneous data to establish joint distributions of waves and currents for design, an extensive metocean measurement programme has been performed over a period of approximately five years at several locations in the northern North Sea. A brief description of the measurement programme is given. The measured current data have been found to be more inaccurate than the specified accuracy of the instruments. However, the measured current data still give a good over-all description of the current conditions. At the southernmost locations, wind-driven currents, i.e. inertial oscillations, are the governing current conditions and contribute to larger current speed during summer than in the spring and fall, both operational and extreme. At all locations, year-to-year variation in estimated extreme current speeds based on different individual years are larger than expected, indicating that current measurements for considerably more than one year is required for reliable estimates of extreme current conditions for design of offshore structures. Sensitivity studies of the ultimate limit state (ULS) load on a jacket suggest the possible gain of accounting for the simultaneous occurrence of metocean parameters. The Norwegian design regulations seem to be conservative, at least regarding ULS. These results highlight the need for a better understanding of the current conditions in order to account for the uncertainties associated with these in design of offshore structures. Highlights: Measured current data is found to be more inaccurate than the specified accuracy of the instruments. As large inter-annual current speed variations are evident, more than 1 year of measured currents are recommended in design. Sensitivity studies of the ULS load on a jacket suggest a possible gain of accounting for joint metocean parameters.